2022
DOI: 10.1038/s41598-022-13729-6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive comparison of treatments for controlling the large pine weevil (Hylobius abietis) in Central Europe

Abstract: Adults of the large pine weevil (Hylobius abietis) cause serious damage to coniferous seedlings and are among the most important forest pests in Europe. Seedling protection by chemicals is gradually being restricted or banned for environmental reasons, and non-chemical alternatives are therefore needed. In this 3-year study, we compared the following five treatments for protecting Norway spruce seedlings against H. abietis in the Central European mountains where the weevil is especially abundant: alpha-cyperme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Insecticide treatment is currently still used for seedling protection in several European countries (Hardy et al 2020, Galko et al 2022, Thomas et al 2022, despite serious concerns for the environment and health of forest workers associated with their use (Mian and Mulla 1992, Kolmodin-Hedman et al 1995, Pisa et al 2015. However, in Swedish forestry, protection with insecticides has been almost completely phased out and replaced by stem coatings that provide physical protection for the seedlings, and similar changes in practices can be expected in other countries (Nordlander et al 2009, Skogsstyrelsen, 2021, Luoranen et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insecticide treatment is currently still used for seedling protection in several European countries (Hardy et al 2020, Galko et al 2022, Thomas et al 2022, despite serious concerns for the environment and health of forest workers associated with their use (Mian and Mulla 1992, Kolmodin-Hedman et al 1995, Pisa et al 2015. However, in Swedish forestry, protection with insecticides has been almost completely phased out and replaced by stem coatings that provide physical protection for the seedlings, and similar changes in practices can be expected in other countries (Nordlander et al 2009, Skogsstyrelsen, 2021, Luoranen et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The various countermeasures differ in effectiveness, costs and environmental impact, but none are ideal for all situations. Therefore, an early damage risk assessment that could be used to adjust the countermeasures to maximize their cost-effectiveness and minimize their environmental impact would be highly valuable (Wilson and Day 1994, Heritage and Moore 2001, Paraschiv 2020, Fedderwitz et al 2022, Galko et al 2022). However, current assessments are usually regional and based on forest owners' previous experiences.…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of insecticides is now being banned or phased out in many countries due to environmental concerns ( Nilsson et al., 2010 ). In their place, integrated pest management incorporating soil scarification, physical stem protection, and other measures may be effective in reducing pine weevil damage ( Dillon and Griffin, 2008 ; Galko et al., 2022 ). Yet, another and perhaps more cost-effective protection measure could be to stimulate the trees’ own defenses using defense elicitors.…”
Section: Introductionmentioning
confidence: 99%
“…The protection of reforested areas from the pine weevil (H. abietis) is one of the largest problems in forest management in many European countries (Nordlander et al, 2011;Willoughby et al, 2017;Tudoran et al, 2021;Galko et al, 2022). Our experiment showed that in the coniferous forests of central Europe, all clearcuts with fresh conifer stumps could be impacted by many pine weevils.…”
Section: Implications For Forest Managementmentioning
confidence: 73%
“…For the experiment, we chose 1-year-old clear-cuts because these are the areas where seedlings are most threatened in central Europe. Over time, their vulnerability decreases (Örlander et al, 1997;Örlander and Nilsson, 1999;Nordlander et al, 2011;Paraschiv, 2020;Galko et al, 2022). The clear-cuts contained seedlings of European forests' three main economic tree species.…”
Section: Feeding On Seedlingsmentioning
confidence: 99%